Health and nutritional aspects of sustainable diet strategies and their association with environmental impacts: A global modelling analysis with country-level detail - Springmann, Marco; Wiebe, Keith D.; Mason-D'Croz, Daniel; Sulser, Timothy B.; Rayner, Mike; Scarborough, Peter (Elsevier, 2018)
Sustainable diets are intended to address the increasing health and environmental concerns related to food production and consumption. Although many candidates for sustainable diets have emerged, a consistent and joint environmental and health analysis of these diets has not been done at a regional level. Using an integrated health and environmental modelling framework for more than 150 countries, we examined three different approaches to sustainable diets motivated by environmental, food security, and public health objectives.